Measurement of the cosmogenic activation of germanium detectors in EDELWEISS-III - Armengaud, E; Arnaud, Q; Augier, C; Kraus, H (Elsevier, 2017)
We present a measurement of the cosmogenic activation in the cryogenic germanium detectors of the EDELWEISS III direct dark matter search experiment. The decay rates measured in detectors with different exposures to cosmic rays above ground are converted into production rates of different isotopes. The measured production rates in units of nuclei/kg/day are 82 ± 21 for 3H, 2.8 ± 0.6 for 49V, 4.6 ± 0.7 for 55Fe, and 106 ± 13 for 65Zn. These results are the most accurate for these isotopes. A 90% C.L. lower limit on the production rate of 68Ge of 71 nuclei/kg/day is also presented. They are compared to model predictions present in literature and to estimates calculated with the ACTIVIA code.